The association of fraser photinia and its beneficial bacterium (PGB_invit) provided in vitro storage without subculture - Sah, Irmak; Akdemir, Hulya; Kaya, Ergun; Akkaya, Ozlem; Ciftci, Yelda Ozden (Springer, 2019)
Endophytes play crucial roles due to their beneficial influence on plant development, growth, fitness, and diversification. Due to these important capabilities, they have received attention from the scientific community and many papers have been published recently about their beneficial role in in vivo and in vitro plant propagation. However, up to now, there is no research on utilization of these microbial endophytes in prolongation of in vitro storage. Thus, the aim of this study is to assess the influence of fraser photinia associated and putatively endophytic bacterium (Plant Growth Bacteria_ in vitro; PGB_invit) on in vitro storage of its host. When pure strain of the bacterium was inoculated, it enabled the storage of microshoots up to 16 months at 25 degrees C without requiring periodic subculture while control (unincubated with PGB_invit.) microshoots died after 2 months of storage without subculture as in vitro plant cultures definitely need periodic subcultures (once in every 4-6 weeks) in order to renew media and gaseous atmosphere. Moreover, while the presence of virulence (vir D1), auxin (aux1), and cytokinin (ipt) production genes was confirmed in plasmid DNA of the bacterium, nitrogen fixing gene (nifH) was detected by the PCR analysis using bacterial culture. Overall results demonstrated that with these capabilities PGB_invit could be useful for in vitro conservation of fraser photinia. Key messageThe novelty is the supplementation of in vitro plant growth without either periodic renewal of the media or decreasing the culture temperature by means of a beneficial plant-bacterium interaction.
Keywords: Aux1; Endophytic; Ipt; NifH; Plant growth promoting bacterium